2015
DOI: 10.1111/hex.12335
|View full text |Cite
|
Sign up to set email alerts
|

Rational expectations? An explorative study of subjective survival probabilities and lifestyle across Europe

Abstract: Background Subjective survival probabilities (SSPs) are considered relevant in relation to lifestyle as lifestyle improvements may improve health and lower mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 51 publications
9
29
1
Order By: Relevance
“…Older people also tend to overestimate survival. Other studies found a significant variation in subjective survival probabilities across Europe (Rappange, Brouwer, and Exel 2016). Liu, Tsou, and Hammitt (2007) and Mirowsky (1999), comparing subjective to actuarial survival probabilities, argue that respondents who live with children report higher survival expectations.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Older people also tend to overestimate survival. Other studies found a significant variation in subjective survival probabilities across Europe (Rappange, Brouwer, and Exel 2016). Liu, Tsou, and Hammitt (2007) and Mirowsky (1999), comparing subjective to actuarial survival probabilities, argue that respondents who live with children report higher survival expectations.…”
Section: Introductionmentioning
confidence: 95%
“…Physical activity is positively associated with subjective survival probabilities, whereas obesity is negatively associated (Rappange, Brouwer, and Exel 2016;Liu, Tsou, and Hammitt 2007). Further, Khwaja, Sloan, and Chung (2007) note that current smokers in the United States are relatively optimistic, whereas people who have never smoked are relatively pessimistic in their survival predictions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of subjective life expectancy (SLE) is important in the context of economic choice behaviour [1], predicting mortality [2] and investment in future health [3]. Such individual subjective expectations may contain information not captured by their objective, actuarial counterparts [4].…”
Section: Introductionmentioning
confidence: 99%